2015
DOI: 10.1007/s11524-015-9976-x
|View full text |Cite
|
Sign up to set email alerts
|

The Non-linear Health Consequences of Living in Larger Cities

Abstract: Urbanization promotes economy, mobility, access, and availability of resources, but on the other hand, generates higher levels of pollution, violence, crime, and mental distress. The health consequences of the agglomeration of people living close together are not fully understood. Particularly, it remains unclear how variations in the population size across cities impact the health of the population. We analyze the deviations from linearity of the scaling of several health-related quantities, such as the incid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 40 publications
5
53
1
5
Order By: Relevance
“…Existe uma tendência de doenças infecciosas terem incidência mais elevada em municípios maiores, possivelmente em razão de uma maior velocidade de disseminação em ambientes com maior densidade populacional 24 . Neste estudo, o município com maior número de casos notificados foi a capital, São Luís, seguido por Imperatriz, ambos constituem os municípios com maior densidade demográfica do estado 25 , o que pode justificar a maior ocorrência de casos.…”
Section: Discussionunclassified
“…Existe uma tendência de doenças infecciosas terem incidência mais elevada em municípios maiores, possivelmente em razão de uma maior velocidade de disseminação em ambientes com maior densidade populacional 24 . Neste estudo, o município com maior número de casos notificados foi a capital, São Luís, seguido por Imperatriz, ambos constituem os municípios com maior densidade demográfica do estado 25 , o que pode justificar a maior ocorrência de casos.…”
Section: Discussionunclassified
“…Also the populations’ health is graded between urban and rural areas (Rocha et al . ). However, the distribution pattern on the national scale is inconsistent in the current literature: A study conducted in the United States reported a higher accessibility to nurses in rural areas than in urban areas (Graves et al .…”
Section: Discussionmentioning
confidence: 97%
“…Pelo contrário, destacam alguns autores que as cidades apresentam atributos físicos e sociais que podem afetar negativamente a saúde das pessoas (Caiaffa et al, 2008). Assim, por exemplo, as doenças infecciosas tendem a ter sua incidência mais elevada em cidades maiores, potencialmente em razão da maior velocidade de disseminação em ambientes mais densamente povoados (Rocha, 2015).…”
Section: Comentários Finaisunclassified